Death and resurrection in art - De Pascale, Enrico; J. Paul Getty Museum (Los Angeles : J. Paul Getty Museum, 2009)
"This book will examine the iconography of death as well as that of its symbolic opposite - resurrection and rebirth."--Introduction.
The blood and the arrow -- Vanitas vanitatum -- Eros and Thanatos -- Between heaven and earth -- Mistress of the world -- Cult of the dead -- Afterworld -- Rebirth.
Includes bibliographical references (pages 382-384) and index.
Keywords: Death in art -- Dictionaries; Resurrection in art -- Dictionaries